Nosocomial influenza in south-western Swiss hospitals during two seasonal epidemics: an observational study. (March 2021) - Qalla-Widmer, L.; Héquet, D.; Troillet, N.; Petignat, C.; Balmelli, C.; Bassi, C.; Bellini, C.; Chave, J.-P.; Cometta, A.; Christin, L.; Clerc, O.; Daher, O.; et al.
Summary: Background: In Switzerland each year, influenza leads to between 112, 000 and 275, 000 medical consultations. Data on nosocomial influenza infection are limited. Aim: To describe nosocomial cases of seasonal influenza in south-western Switzerland. Methods: This study was conducted during two seasonal influenza epidemics from 2016 to 2018 in 27 acute care public hospitals in south-western Switzerland. During these two time-periods, every patient hospitalized for >72 h who was positively screened by reverse transcription–polymerase chain reaction or antigen detection for influenza was included in the survey. Characteristics of patients included age, sex, and comorbidities. Included patients were followed up until discharge or death. Complications and administration of antineuraminidases and/or antibiotics were registered. Findings: The median influenza vaccine coverage of healthcare workers was 40%. In all, 836 patients were included (98% with type A influenza virus in 2016–2017; 77% with type B virus in 2017–2018). Most patients (81%) had an unknown vaccine status. Overall, the incidence of nosocomial influenza was 0.5 per 100 admissions (0.35 per 1000 patient-days). The most frequent comorbidities were diabetes (20%), chronic respiratory diseases (19%), and malnutrition (17%). Fever (77%) and cough (66%) were the most frequent symptoms. Seventy-one percent of patients received antineuraminidases, 28% received antibiotics. Infectious complications such as pneumonia were reported in 9%. Overall, the all-cause mortality was 6%. Conclusion: The occurrence of nosocomial influenza underlines the importance of vaccinating patients and healthcare workers, rapidly recognizing community- or hospital-acquired cases, and applying adequate additional measures to prevent dissemination, including the timely administration of antineuraminidases to avoid antibiotic use (and misuse).